2007
DOI: 10.1002/nur.20186
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of caregivers' willingness to participate in an intervention research study

Abstract: The purpose of the study was to identify factors that influenced family caregivers' decisions to participate in an intervention research study. In interviews conducted before and after the intervention, caregivers (n=21) described reasons for participation. A focused content analysis was used to examine responses. Themes that emerged included: (a) caregivers recognized a need for help; (b) expectations and motivations toward change; (c) recognition of self worth as caregivers; (d) timeliness of recruitment str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 22 publications
3
51
0
Order By: Relevance
“…Several of the caregivers interviewed for this study identified a "window of recruitment opportunity"-that is, a specific time when participating in a caregiver educational program would be more relevant because of some kind of triggering event (eg, being newly diagnosed, an exacerbation of illness, or a hospitalization). This finding is similar to a finding by Murphy et al 21 that caregivers of people with dementia were willing to participate in a study at a time when they felt they needed the most help and were accepting of that help. Although timeliness may be an important factor for caregivers of people with a variety of diagnoses, triggering events vary depending on the nature and course of the particular diagnosis of the care recipients (eg, whether it is progressive, has exacerbations and "Maybe [include] quotes from other caregivers that have gone through [the study program], especially for things they have dealt with, like maybe anger level" (P3, 127-130).…”
Section: Recommendations To Improve the Recruitment Materialssupporting
confidence: 89%
See 1 more Smart Citation
“…Several of the caregivers interviewed for this study identified a "window of recruitment opportunity"-that is, a specific time when participating in a caregiver educational program would be more relevant because of some kind of triggering event (eg, being newly diagnosed, an exacerbation of illness, or a hospitalization). This finding is similar to a finding by Murphy et al 21 that caregivers of people with dementia were willing to participate in a study at a time when they felt they needed the most help and were accepting of that help. Although timeliness may be an important factor for caregivers of people with a variety of diagnoses, triggering events vary depending on the nature and course of the particular diagnosis of the care recipients (eg, whether it is progressive, has exacerbations and "Maybe [include] quotes from other caregivers that have gone through [the study program], especially for things they have dealt with, like maybe anger level" (P3, 127-130).…”
Section: Recommendations To Improve the Recruitment Materialssupporting
confidence: 89%
“…20 Despite the success of many caregiver education programs, 15,17,18,20 one common problem has been recruiting participants for caregiver education research. 21 Researchers have used a variety of recruitment strategies including convenience sampling, open enrollment, and referral by professionals, but still frequently report encountering problems recruiting participants. 19,20 During a pilot study for an education and self-management program targeting caregivers of people with multiple sclerosis (MS), we experienced similar recruitment challenges despite having used a variety of recruitment strategies (eg, flyers distributed through MS support groups, in public places, and through health-care professionals; announcements in MS society newsletters and local newspapers and on local radio stations; and direct mailing to members of the local MS society).…”
Section: Consent Processmentioning
confidence: 99%
“…were not surprisingly somewhat healthier [19] with respect to sleep disordered breathing with only 3/222 snoring regularly. As the OR was calculated to be high for a not snoring child of four to continue to be not snoring through childhood, we make the assumption that at twelve years, the prevalence of children snoring regularly would be slightly lower than that reported.…”
Section: Discussionmentioning
confidence: 94%
“…Out of the 118 invited families 37 declined enrolment in the study, which is to be expected when the randomization is performed prior to the invitation to the study (28). Since the number of children who did not get enrolled was about the same for TE and TT, no extra analysis of them as a group was regarded as necessary.…”
Section: Not-s Examinationmentioning
confidence: 99%
“…Since the number of children who did not get enrolled was about the same for TE and TT, no extra analysis of them as a group was regarded as necessary. However, the proportion of children with oral motor disturbances might have been slightly higher among the participants than among the children who were not enrolled, reflecting a greater interest in the study for families experiencing the problems to be investigated (28).…”
Section: Not-s Examinationmentioning
confidence: 99%